Biologically active metabolites of Alcaligenes faecalis: diversity, statistical optimization, and future perspectives - Sayed E. El-Sayed; Neveen A. Abdelaziz; Mohammad Y. Alshahrani; Ghadir S. El-Housseiny; Khaled M. Aboshanab (Future Science OA)
Alcaligenes faecalis is a Gram-negative, rod-shaped bacterium that is common in the environment and has been reported to have various bioactive metabolites of industrial potential applications, including antifungal, antibacterial, antimycobacterial, antiparasitic, anticancer, antioxidant activities. In this review, we highlighted and discussed the respective metabolites, pointing out their chemical diversities, purification, current challenges, and future directions. A. faecalis has an industrial role in biodegradation, biosurfactants, and different enzyme production. In this review, the up-to-date various Response Surface Methodology methods (RSM) that can be employed for statistical optimization of the bioactive secondary metabolites have been discussed and highlighted, pointing out the optimal use of each method, current challenges, and future directions.